Taqî al Dîn (1521–1585) - Dosay Gökdoğan, Melek; Uymaz, Tuba (Springer International Publishing, 2020)
Taqi al-Din, definitely one of the most important Ottoman scholars of the 16th century, is known for mostly observatory (Istanbul Observatory) which was established by him, the works which he wrote up there and the observations which he carried out with instruments which he made his own. In that period, observation tools which he made had no lacking than tools in the West; in fact, it is known that he contended against Uraniborg Observatory of Danish Tycho Brahe who lived in the same age and observation tools which he made. In addition to this, he worked in the fields of optics and mathematics and he wrote a book which is called “Al-Turuk al-Saniyya fi al-Âlât al-Ruhâniyya” (Book of the Sublime Methods of Spiritual Machines), about machines. This book in that mechanical clocks, levers, water raising machines, automata and fountains had been designed and described in detail, has a historical importance because of being first and unique treatise of its kind in the Ottomans. In this article, we principally introduced this work.